“Ancestors” and “Relatives” : Ralph Ellison's Family Romance from Invisible Man to Three Days Before the Shooting - (:unkn) unknown (My University, 2017)
My dissertation explores what I call Ralph Ellison's literary “family romance.” I investigate how Ellison's concern with identity politics and novelistic achievement, and his engagement with the ideal of democracy and integration informed his selection of literary patrilineage and led him to reverse the trope of literary lineage by claiming descent from European and white American literary predecessors whom he names his “ancestors,” and by underplaying the influence of his African American forebears whom he names “relatives.” I demonstrate that the ground on which Ellison reverses the trope of literary kinship relates to his view of literature as inherently integrationist. Ellison, through his non-fiction and the polyphony of allusions in Invisible Man and his posthumous novel Three Days Before the Shooting, enters into a revisionist dialogue with his ancestors and his relatives. I explore this through the example of Ernest Hemingway, André Malraux and Richard Wright. I argue that Ellison's chosen ancestors provided him with models of form that he used to re-inscribe or subvert models of content presented by both his ancestors and his relatives, and that Ellison embodies these influences by Signifyin(g) on the texts of both sources wherein he criticizes their representation of the African American and his experience, through the use of the multiple strategies of signifying such as literary allusion, repetition with variation, parody and pastiche
Keywords: African Research